Analisis Pola Asuh Orang Tua dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 - Finka Nursiyamah; A.Y. Soegeng Ysh; Filia Prima Artharina (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine and describe parenting patterns in online learning for fifth graders at SD Negeri Ngiyono, Blora Regency during the Covid-19 pandemic. This research method is qualitative research using data collection techniques in the form of questionnaires, interviews, observations, and documentation. Based on the findings of the research, it can be concluded that the problems in this study are due to changes in the pattern of education, which initially learned face-to-face at school, turned into online learning at home. With this, very important the role of parents in accompanying children to study online at home so that appropriate parenting patterns are needed according to the needs of children. From 15 parents of fifth grade students at SD Negeri Ngiyono, Blora Regency, 10 parents applied democratic parenting, 3 parents applied authoritarian parenting, and 2 parents applied permissive parenting. Based on the results of the research, suggestions that can be conveyed are that parents and students are expected to be able to establish good and harmonious relationships such as accompanying children to learn, be open, giving attention and support in online learning during the Covid-19 pandemic by implementing appropriate parenting patterns in accordance with children's needs.